Temperature-dependent fine structure splitting in InGaN quantum dots - Wang, T; Puchtler, T; Zhu, T; Jarman, J; Kocher, C; Oliver, R; Taylor, R (AIP Publishing, 2017)
We report the experimental observation of temperature-dependent fine structure splitting in semiconductor quantum dots using a non-polar (11-20) a-plane InGaN system, up to the on-chip Peltier cooling threshold of 200 K. At 5 K, a statistical average splitting of 443 ± 132 μeV has been found based on 81 quantum dots. The degree of fine structure splitting stays relatively constant for temperatures less than 100 K and only increases above that temperature. At 200 K, we find that the fine structure splitting ranges between 2 and 12 meV, which is an order of magnitude higher than that at low temperatures. Our investigations also show that phonon interactions at high temperatures might have a correlation with the degree of exchange interactions. The large fine structure splitting at 200 K makes it easier to isolate the individual components of the polarized emission spectrally, increasing the effective degree of polarization for potential on-chip applications of polarized single-photon sources.